2014
DOI: 10.1007/s12185-014-1677-9
|View full text |Cite
|
Sign up to set email alerts
|

A role for peripherally inserted central venous catheters in the prevention of catheter-related blood stream infections in patients with hematological malignancies

Abstract: Central venous catheter-related blood stream infections (CR-BSIs) are a serious complication in patients with hematological malignancies. However, it remains unclear whether there is a difference in the rate of CR-BSI associated with the conventional type of central venous catheters (cCVCs) and peripherally inserted CVCs (PICCs) in such patients. To address this question, we retrospectively investigated the incidence of CR-BSIs associated with PICCs versus cCVCs in patients with hematological malignancies. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
3
26
0
1
Order By: Relevance
“…Infections are one of the most serious complications to consider among cancer patients, owing to both the treatment and malignancy conditions of the disease [24] and the conditions related to the venous access itself [20]. Regarding their incidence according to the type of central access used, the evidence is still controversial, as some studies performed in cancer patients showed significantly lower rates with PICCs versus CICCs (1.23 vs. 5.3/100 days of catheter use) [25] or a lower incidence with PICCs in outpatients [26], while other data suggest that in the short term the incidence of infection is similar.…”
Section: Main Catheter-associated Complicationsmentioning
confidence: 99%
“…Infections are one of the most serious complications to consider among cancer patients, owing to both the treatment and malignancy conditions of the disease [24] and the conditions related to the venous access itself [20]. Regarding their incidence according to the type of central access used, the evidence is still controversial, as some studies performed in cancer patients showed significantly lower rates with PICCs versus CICCs (1.23 vs. 5.3/100 days of catheter use) [25] or a lower incidence with PICCs in outpatients [26], while other data suggest that in the short term the incidence of infection is similar.…”
Section: Main Catheter-associated Complicationsmentioning
confidence: 99%
“…2 Both catheter types terminate in the junction between the superior vena cava (SVC) and atrium of the heart. 2,3 PICCs and CICCs, each having unique benefits, are commonly used to deliver medication in various settings and patient populations, including intensive care units (ICUs), 47 for oncology patients, 1,810 and in-home parenteral nutrition (HPN). 8,11 These can be used for both short- and long-term venous access.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to CRBSI, the rate of PICC‐related thrombosis exhibited a statistically significant decrease over the last decades. Less than 7% of PICC‐related thrombosis incidence rate was reported in several recent studies (Chopra, Kuhn, Ratz, Lee, & Krein, ; Patel et al., ; Sakai et al., ). Nevertheless, researches have demonstrated a correlation between deep vein thrombosis and malignancies (Chopra, Anand, et al., ; Fallouh, McGuirk, Flanders, & Chopra, ; Hingorani et al., ), which is consistent with our results of apparently higher incidence rate of PICC‐related thrombosis.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, 11.4% of patients had a PICC‐related thrombosis in our study. The previous study on nonhospitalised cancer patients showed a thrombosis rate of 1.1%, whereas another study reported that 8.9% of patients with haematological malignancies developed CRBSI (Cotogni et al., ; Sakai et al., ). This difference may suggest that PICC‐related thrombosis is more prevalent in haematological malignancies than solid tumours.…”
Section: Discussionmentioning
confidence: 95%